Alternative Lime Based Grouts Used in Re-pointing of Deteriorated Ancient Mortars and their Structural Effects on Composite Unreinforced Masonry Walls of Mekaad Radwan, Ottoman Cairo, Egypt (Case Study). (14th July 2016) - Ali, Mona F.; Moussa, Abubakr; Abdelhafez, Mahmoud
Abstract: Mortars and plasters of Mekaad Radwan are badly affected by decay hazards, therefore; they were studied by means of XRD and polarized microscope to detect their chemical composition, physical and petrographic properties, in addition to identify their characteristics. The analyses revealed gypsum mixed with lime as dominant component with some aggregates of sand particles, sodium chloride was detected in all the studied samples. Standardized alternative mortars were prepared, exposed to artificial aging and tested in order to select the most suitable type to replace the old mortars and plasters at Mekaad Radwan.